Strategi Komunikasi Lingkungan Berbasis Partisipasi Masyarakat dalam Rehabilitasi Mangrove di Pesisir Kabupaten Pinrang (Studi Kasus Dusun Tanroe) - Cellu, Muh. Chaerul; Cangara, Hafied; Unde, Andi Alimuddin (Program Studi Magister Manajemen Lingkungan, 2024)
Environmental issues on the coast are of concern because of their important existence, but environmental conditions on the coast, especially mangrove forests, are increasingly critical Based on Clark Labs data, the extent of mangrove conversion to ponds from 1999 to 2018. The on going community participation in the mangrove rehabilitation program has its dynamics because it involves many parties. The parties involved include local governments (Forestry Service, UPT Sawitto, and Fisheries Service), farmers, village governments, and communities. During the implementation of the program activities, the main issues encouraging community participation in mangrove rehabilitation such as analysis, strategy, mobilization, action, evaluation, and sustainability are very interesting to be studied further. This research uses qualitative research with a case study approach. The unit of analysis is the mangrove rehabilitation program. Key data were collected through in-depth interviews with key informants. For the data triangulation process, observation of mangrove rehabilitation sites was carried out to complete the research data. Furthermore, the data is analyzed using data reduction, data presentation, and conclusion. The result of this study is an evaluation of community participation in the mangrove rehabilitation program in Tanroe Hamlet, Bababinanga Village, while some issues have not been satisfactory such as participation in evaluation and participation in decision-making. Furthermore, developing a communication strategy run by the Pinrang Regency Government is very good for the short term. In the long term, it has not yielded significant results in some areas of the rehabilitation program. This is influenced by several things, including land rehabilitation and empowerment by communicators, extension programs and public campaigns, community participation in planning and decision-making, diverse communication media, formation of working groups and training, monitoring, and feedback. In principle, the practice carried out is good but still at the exploration stage.